Analysis of Student's Creativity Value and Process Skills through Learning Strategies Guided Inquiry - Muchsin Muchsin; Hamdi Hamdi (UNIVERSITAS SERAMBI MEKKAH, 2021)
This study aims to analyze the effect of learning with guided inquiry strategies on creativity and science process skills at SMA Negeri 1 Bandar Baru. This research uses a quantitative descriptive approach with quasi experimental research techniques. The design used in this study was a non-equivalent control group design. Data collection was grouped into 2 groups, namely the experimental group and the control group. The number of samples in this study were 50 students for the experimental class and 52 students for the control class. The research instruments were creativity tests and science process skills tests. The value of the students' creativity test results at a significance level of 0.05 obtained that the sig value was 5.965 1.98 (tcount ttable) and Sig (2-tailed) 0.000 0.05 indicating that the data was significant or significantly different between the experimental class and the class control. Hypothesis testing with the SPSS version 23.0 for windows program at a significant level of 0.05 was obtained; The value of students 'science process skills shows that t-count t-table at a significant level of 0.05, namely 6.0551.98, indicates that there is an effect of guided inquiry strategies on students' science process skills. This shows that the science process skills of students who have a high level of creativity with students who have a low level of creativity, where students who have a high level of creativity obtain higher process skills than students who have a low level of creativity and between students' creativity and science process skills.